Testing the psychometric properties of the self-compassion instrument in college students - Riesa Rismawati Siddik; Juntika Nurihsan; Nandang Budiman; Ipah Saripah (Jurnal Konseling dan Pendidikan, 2026)
Although research on self-compassion has increased, there is still a lack of empirically validated self-compassion instruments that demonstrate measurement fairness across gender and cultural backgrounds in specific institutional contexts. This study aimed to develop a Self-Compassion Inventory (SCI) and examine its psychometric properties using a sample of university students from IKIP Siliwangi, Bandung. A total of 514 undergraduate students participated in the study through an online survey administered via Google Forms, consisting of 145 male students (28.2%) and 369 female students (71.8%), representing diverse cultural backgrounds, including Bali, Cirebon, Betawi, Jawa, Batak, Minangkabau, and Sunda ethnicities. The SCI was constructed based on three core dimensions of self-compassion: Self-Kindness versus Self-Judgment, Common Humanity versus Isolation, and Mindfulness versus Over-Identification. Data were analyzed using the Rasch measurement model to evaluate item fit, dimensionality, reliability, and differential item functioning (DIF) across gender and cultural groups. The findings indicate that the SCI functions as a valid, reliable, and fair instrument for assessing self-compassion among university students. Most items exhibited good model fit, and the instrument showed stable item calibration. DIF analysis revealed no significant cultural bias, while limited gender-based DIF was identified and addressed during item refinement.